Sufi Masters and the Creation of Saintly Spheres in Medieval Syria - Ephrat, Daphna (Medieval Islamicate World, 2021)
This book explores the lives of Sufi masters who functioned as embodiments of Islamic sainthood and left a lasting mark on the land. These figures lived in the ancient cities of Syria and their surrounding towns and villages during a formative period in the social history of Syrian Sufism and the spiritual tradition of Islam.